Analysis of the Influence of Training and Development and Career Opportunities on the Work Motivation of Human Resources in the Manufacturing Sector - Desfitrina Desfitrina; Zulfadhli Zulfadhli (Westscience Press, 2026)
The manufacturing sector in Indonesia faces increasing challenges related to technological transformation, global competition, and the need for highly competent and motivated human resources. Employee motivation has become an essential factor in maintaining organizational productivity and competitiveness, particularly in industries that rely heavily on workforce effectiveness. This study aims to analyze the influence of training and development and career opportunities on employee work motivation in the manufacturing sector in Indonesia. This research employs a quantitative approach using survey data collected from 180 employees working in manufacturing companies. Data were obtained through a structured questionnaire measured using a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The analytical methods included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that training and development have a positive and significant effect on employee work motivation. Career opportunities also have a positive and significant influence on work motivation. Furthermore, both variables simultaneously explain 52.4% of the variation in employee motivation. These findings demonstrate that effective employee development programs and clear career advancement pathways are important factors in strengthening workforce motivation in the manufacturing sector. This study contributes to human resource management literature by providing empirical evidence regarding the role of organizational development practices in enhancing employee motivation and offers practical implications for manufacturing organizations in Indonesia to design more effective workforce management strategies.